Metabolic analysis of mouse bone-marrow-derived dendritic cells using an extracellular flux analyzer - Gotoh, Kazuhito (STAR Protoc, 2021)
Dendritic cell (DC) maturation induced by Toll-like receptor (TLR) agonists requires the activation of downstream metabolic changes. Here, we provide a detailed protocol to measure glycolysis, mitochondrial respiration, and fatty acid oxidation in mouse bone-marrow-derived DCs with the Seahorse XF24 extracellular flux (XF) analyzer. XF analysis with the Seahorse bioanalyzer has become a standard method to measure bioenergetic functions in cells, and this protocol can be adapted to other immune cells. For complete information on using this protocol, please refer to Gotoh et al. (2018).